Saling Ketergantungan Antara Data Governance Terhadap Data Manajemen Dan Pengaruhnya Terhadap Kinerja Lembaga Bank Mandiri - Embun Febryanti Panggabean; Muhammad Irwan Padli Nasution (Jurnal Sistem Informasi dan Ilmu Komputer, 2023)
Effective data governance is critical for companies to ensure that the use of data in their operations has a positive impact on overall performance and enables the fulfillment of legal obligations regarding the use and management of data and regulatory requirements. Data services are a core business function of the agency, therefore it is very important for companies to give high priority to providing reliable data quality. By avoiding duplication, ensuring correctness, validity and ongoing accessibility, data governance is critical to obtaining high-quality data. Currently, financial institutions have not formally adopted an effective data governance policy. Therefore, a study was conducted to examine the relationship between data governance and data management and how this affects Bank Mandiri's performance. The research method used is qualitative and is based on an in-depth examination of the relevant literature, including books and journals. In addition to determining the influence of data governance on management practices and the overall performance of a bank, this study aims to gain insights into the relationships and dependencies between data governance and data management. The findings of this study indicate that despite having similar objectives, data management and data governance show interdependence and reciprocity in various aspects.